41 PROFILING PHYSICAL ACTIVITY AND SARCOPENIA AMONG OLDER ADULTS ATTENDING A PHYSIOTHERAPY SERVICE DURING THE COVID-19 PANDEMIC: A MIXED METHODS STUDY. (25th October 2022) - Tague, AM; Keating, L
Abstract: Background: Reduced physical activity (PA) and increased levels of sarcopenia are possible consequences of the COVID-19 pandemic among older adults. During the pandemic, 26% of people over 70 were inactive. This mixed-methods study aimed to profile PA and sarcopenia levels among older adults attending a primary care physiotherapy service during the pandemic and to explore their experiences of PA. Methods: Adults over 70 years of age attending a primary care physiotherapy service were invited to participate between September 2021 - January 2022. PA and levels of sarcopenia were captured using the International Physical Activity Questionnaire Short Form and the SARC-F. One-to-one semi-structured telephone interviews were conducted with a sample of the group and analysed using thematic analysis. The Irish College of General Practitioners granted ethical approval. Results: 59 participants (35 females) participated in the cross-sectional study (median age: 79.3; IQR: 12 years). Ninety-one percent of participants (n=54) followed cocooning restrictions. Fifty-six percent (n=33) of participants had low PA levels (95% CI: 43-69%), and 56% (n=33) scored 4 or more on the SARC-F (95% CI: 43-69%), which is predictive of sarcopenia. Ten participants (7 females) completed an interview (median age: 75.4; IQR: 5years). Four themes emerged; 1) a sudden in change in PA levels, 2) the impact of cocooning measures on PA levels, 3) barriers to PA and 4) enablers of PA during the COVID-19 pandemic. Conclusion: Low PA levels and high levels of sarcopenia were identified among older adults attending a primary care physiotherapy service. Participants were uncertain if they would return to their pre-pandemic PA levels due to slowness of movement and fear of COVID-19. There is a need to address these low PA levels as society enters a new post-pandemic phase.